A tailored molecular profiling programme for children with cancer to identify clinically actionable genetic alterations. (November 2019) - George, Sally L.; Izquierdo, Elisa; Campbell, James; Koutroumanidou, Eleni; Proszek, Paula; Jamal, Sabri; Hughes, Deborah; Yuan, Lina; Marshall, Lynley V.; Carceller, Fernando; Chisholm, Julia C.; Vaidya, Sucheta; et al.
Abstract: Background: For children with cancer, the clinical integration of precision medicine to enable predictive biomarker–based therapeutic stratification is urgently needed. Methods: We have developed a hybrid-capture next-generation sequencing (NGS) panel, specifically designed to detect genetic alterations in paediatric solid tumours, which gives reliable results from as little as 50 ng of DNA extracted from formalin-fixed paraffin-embedded (FFPE) tissue. In this study, we offered an NGS panel, with clinical reporting via a molecular tumour board for children with solid tumours. Furthermore, for a cohort of 12 patients, we used a circulating tumour DNA (ctDNA)–specific panel to sequence ctDNA from matched plasma samples and compared plasma and tumour findings. Results: A total of 255 samples were submitted from 223 patients for the NGS panel. Using FFPE tissue, 82% of all submitted samples passed quality control for clinical reporting. At least one genetic alteration was detected in 70% of sequenced samples. The overall detection rate of clinically actionable alterations, defined by modified OncoKB criteria, for all sequenced samples was 51%. A total of 8 patients were sequenced at different stages of treatment. In 6 of these, there were differences in the genetic alterations detected between time points. Sequencing of matched ctDNA in a cohort of extracranial paediatric solid tumours also identified a high detection rate of somatic alterations in plasma. Conclusion: We demonstrate that tailored clinical molecular profiling of both tumour DNA and plasma-derived ctDNA is feasible for children with solid tumours. Furthermore, we show that a targeted NGS panel–based approach can identify actionable genetic alterations in a high proportion of patients. Highlights: The hybrid-capture panel gives reliable results from as little as 50 ng of DNA extracted from formalin-fixed paraffin-embedded tissue. A tailored sequencing approach identifies ≥1 genetic alteration in 70% of samples and potentially actionable genetic alterations in 51% of patients. In paired samples, from different treatment time points, there were differences in the genetic alterations detected.